POLA KOMUNIKASI GURU DI RUANG PUBLIK SEKOLAH - Adam Latuconsina (IAIN Ambon, 2019)
The communication of teachers in the public room is one of the strategies for transferring the lesson material to the participants. Done through forms of communication so that students are motivated to build dialogue and interaction as part of the learning process. The results of this research show that the teacher's community pattern in the school public room has been effectively and intensely: [1] Process of communication of teachers conducted through observations of behavioral students to know the ins and outs of psychology every learner. Then the teacher seeks to establish good communication with the aim of attracting sympathy. This is done because some learners who are less eager in the learning process, such as: not focused on learning, can not memorize in front of the class, and pay less attention to school assignments. [2] Teacher communication patterns used in learning are: personal and group communication patterns include; [a] Such verbal communication, delivering the material directly to the learners. [b] Non-verbal, such as: demonstrated behavior, neat dressing style, style of speech and the way of dialogue with teachers when delivering material. [3] Media such as: using books relating to the material being taught. With this teacher's communication pattern gives a positive impact on learners so that they can be motivated to follow the subject matter. Keywords: teacher communication pattern, student motivation